Nondestructive Determination of Climate‐Specific Degradation Patterns for Photovoltaic‐Module Encapsulation. Issue 1 (28th October 2013) - Peike, Cornelia; Hoffmann, S.; Heck, M.; Kaltenbach, T.; Weiß, K.‐A.; Köhl, M.
Abstract During the service life of a PV module, various different degradation mechanisms can be induced. Polymer degradation depends strongly on the external conditions, which are determined by the climate and the specific conditions of the module. Nondestructive measurements of the degradation behavior of the PV‐module encapsulation material ethylene vinyl acetate (EVA) were performed. We present results of Raman spectroscopic measurements on full‐sized PV modules from several different PV module manufacturers, which were exposed outdoors in different climates for up to three years. This way, the different degradation mechanisms that are induced under the influence of different climatic conditions during outdoor exposure could be investigated. It was found that the degradation pattern, detected by Raman spectroscopy, was rather similar for the investigated climates, but the extent of polymer degradation was found to be higher for tropic and arid climates than for moderate or mountain climates.